Implementation of the Independent Curriculum in Science Learning in Elementary Schools - Desi, Desi Indriyani; Meilina, Fitria; Khairiyah, Karunia Yulinda; Sanusi, Rahmat (The Future of Education Journal, 2025)
This study aims to describe the implementation of the Independent Curriculum in science learning in elementary schools. The focus of the study includes how the principles of the Independent Curriculum are applied, the challenges faced by teachers, and the strategies used to deliver science material contextually and meaningfully. This study used a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation studies. The results indicate that the implementation of the Independent Curriculum in science learning provides space for students to explore science concepts actively, collaboratively, and project-based. However, challenges remain regarding teacher preparedness and limited infrastructure. This study recommends strengthening teacher competencies, providing contextual learning resources, and synergy between schools, parents, and the community to support science learning based on the Independent Curriculum.